B2B E-Commerce:Utilizing Electronic Marketplaces for Procurement - Ram, Manoranjan P.; Rangaswamy, A.; Jainila Sundari, R. (Indian Journal of Marketing, 2009)
An electronic business to business procurement is an inter-organisational information system through which multiple buyers and sellers interact to accomplish market-making activities for corporate purchases. In this study, the extent to which organizations had plans to utilize electronic market places for purchases was investigated. A survey was conducted in Delhi and NCR. Survey results indicate that most organizations had plans; only three per cent had no plans while thirty four percent had concrete plans to utilize electronic market places for purchases. Responding organizations planned to purchase significantly more indirect goods than indirect services on electronic places. The main benefit expected from utilizing electronic market places for purchased was reduced transaction costs. Strategic importance of business to business electronic markets can significantly predict the extent to which responding organizations had plans to utilize electronic market places for purchases.